Control of marine leeches infecting hybrid grouper Epinephelus fuscoguttatus >< E. lanceolatus with garlic Allium sativum powder - Aminatul Zahra; Dwi Septiani Putri (Jurnal Akuakultur Indonesia)
Grouper has a large market demand and to meet this, the intensification of grouper cultivation is being carried out more massively. This situation increases the spread of diseases, one of which is sea leeches. This study aimed to obtain the concentration and duration of immersion garlic powder for the control of leeches that infects hybrid grouper (Epinephelus fuscoguttatus >< E. lanceolatus). This study used a factorial randomized design (concentration factor and garlic soaking time factor) with nine treatments and three replications. The treatment in this study was a combination of 0 g/L 0,375 g/L, and 0,750 g/L garlic powder concentration and immersion times of 20 minutes, 40 minutes, and 60 minutes. The results showed that concentrations of 0.375 g/L and 0.750 g/L were able to significantly reduce the intensity of leeches infecting hybrid grouper, namely 7.43% and 13.29%, respectively. The interaction between concentration and duration of immersion garlic powder on the percentage decrease in intensity was not significantly different. Immersion of garlic powder for 60 minutes was able to reduce the intensity of the leech by 9.56% and the results were significantly different with the immersion time of 20 and 40 minutes. However, the concentration and duration of soaking garlic powder were not able to reduce the prevalence of hybrid grouper infected with leeches. The R2 value of 0.748 means that there is a relationship between garlic powder concentration and the decrease in leech intensity in hybrid grouper. Powder garlic concentration of 0.750 g/L and immersion time of 60 minutes was able to reduce the intensity of leeches in hybrid grouper, but it was not effective in reducing the prevalence of fish infected with leeches.